Tangkas Lawan Pandemi COVID-19: Pelajaran dari Kearifan Lokal Aceh dan Kesiapan Aceh Hadapi Pandemi COVID-19 - Herlina J. EL- Matury; Fatma Lestari; Selamat Ginting; Saiful Batubara; Bunga Mari Sembiring (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
The Acehnese have a long history of disaster preparedness due to their experience with natural disasters, including tsunamis and epidemics. During the COVID-19 outbreak, Aceh has benefited from many lessons from collaboration at the central, regional, and village/gampong levels by the government and PENTAHELIX actors such as communities, academics, religious leaders, mass media, entrepreneurs, philanthropy, and local wisdom combined with modern technology for cross-border mobility. Handling COVID-19 in Aceh has strengths in the form of unique local wisdom and privileges of Aceh Province. This paper provides the best lessons on readiness, response, recovery efforts, a new disaster risk reduction approach, and future recommendations from the Aceh Province during the COVID-19 pandemic in 2020. Acehnese’s local wisdom is salt, water in the jar (le lam guci), henna on fingers (pakek gaca), chewing betel leaf (pajoh ranup), burning rice (tuet leumang), isolation of the sick, and hold a prayer, is obtained from the plague experience in the past.